The Role of Social Capital to Strengthen Market Segmentation Strategy (Study on Sadariyah Cassava Crackers Business in Blitar) - Fiernaningsih, Nilawati; Widayani, Anna; Himmah, Mahmudatul; Zubaidi; Akhsanu Takwim, R N; Junus, Mochammad; Ismanto (Universitas Nahdlatul Ulama Blitar, 2025)
Micro, Small, and Medium Enterprises (MSMEs), especially in the snack industry sector, such as cassava crackers, play an important role in supporting the Indonesian economy through job creation and contribution to Gross Domestic Product (GDP). However, MSMEs often face challenges in maintaining and expanding their market share amid increasingly fierce competition. This study aims to analyse the role of social capital in strengthening market segmentation strategies at Sadariyah Cassava Crackers Business in Blitar Regency. The method used is descriptive qualitative, with data collection techniques through in-depth interviews, direct observation, and documentation. The informants in this study were five people, consisting of business owners, employees, regular customers, and local community leaders. The results show that social capital, which includes strong social networks, trust between businesses and consumers, and the application of local social norms such as gotong royong, contributes significantly to expanding the market and maintaining customer loyalty. The market segmentation strategy applied based on demographic, psychographic, and consumer behaviour factors proved effective in reaching various customer groups. These findings imply that the synergy between social capital and the right market segmentation strategy can improve the competitiveness of MSMEs in a competitive market and promote sustainable business growth.